Correlation of BMP2 with Degree of Osteitisin Primary CRS with and without nasal Polyps - Handoko, Edi; Santoso, David; Maharani, Iriana; P.W, Yuyun Yueniwati; Agustina, Tanti (Biology, Medicine, & Natural Product Chemistry, 2025)
Chronic rhinosinusitis (CRS) is an inflammation of the nasal mucosa and paranasal sinuses, persisting for over12 weeks. CRS involves a remodeling process and opacification known as osteitis, resulting from type 2 and non-type two inflammation. Osteitis severity is assessed using CT scans and the Global Osteitis Scoring Scale (GOSS). Bone morphogenetic protein-2 (BMP-2) is crucial in osteogenesis and bone remodeling. However, no research has shown a relationship between BMP-2 concentration and osteitis degree, as measured by GOSS, in CRS patients with or without nasal polyps. The objective of this study is to analyze the relationship between BMP-2 concentration and osteitis degree measure with GOSS in primary CRS. A cross-sectional analytic observational study was conducted using primary RSK as the study population. BMP-2 concentration, a marker for bone remodeling, used ELISA. The osteitis of the paranasal sinus walls was assessed with a CT scan and quantified using the GOSS method.  The study included 44 patients, with 8 of them serving as the control group. It was found that BMP-2 concentration (ng/mL) had a linear relationship with the GOSS degree in patients with CRS, showing a correlation of 0.583 (deviation >0.05). Further analysis revealed a significant correlation between BMP-2 concentration and GOSS, with a coefficient of 0.857 (considered very significant, in the range of 0.76-0.99). This strong correlation indicates that as BMP-2 concentration strongly correlates with the occurance of osteitis, which were measured by GOSS. BMP-2, as a marker for osteitis in CRS, shows a significant and linear correlation with the severity degree of osteitis measured by GOSS.